PENGEMBANGAN MEDIA AUDIO VISUAL MATERI NARRATIVE TEKS UNTUK PEMBELAJARAN BAHASA INGGRIS DI SMA - Laily, Riska; Asyhar, Rayandra; Rachmawati, Rachmawati (Program Magister Teknologi Pendidikan Universitas Jambi, 2012)
This research study is aimed to: (1) produce media audio visual english instructional for Senior High School, (2) study of process developing audio visual media of narrative text learning english for SMA, (3) provide audio visual media as instructional alternative for teachers in teaching learning process. This study was developmental research. The data collected in this research included instruments validation for the expert of english education and the expert of instructional media, and questionnaire sheet for the one-to-one try out, the small group try-out, and the field try-out. The data were analyzed by using descriptive analysis. The findings of the study are: (1) the development of audio visual media learning english for senior high school proceeded in six steps, namely, analyzing, designing, producing, validating, revising, and trying-out, (2) the quality of developed media viewed from the aspect of content and instructional are good, (3) he aspect of attractiveness shows thar developed instructional media was interesting, in the one-to-one try out, of the three students observed, two students indicated that the product attraction was interesting, and one student indicated that the product attraction was very interesting, sis students for the small group try-out indicated that the product was interesting, and in the field group try out from fifteen students indicated 87% stated that product was interesting, (4) based on the observation showed that audio visual media can be used as alternative instructional media. Audio visual media products needed in creating a variety of learning and motivate students in learning the material in accordance with the demands of the curriculum. It is expected a further study on this development, in order to develop better products Kata kunci: audio visual media, narrative text